PENGARUH LAMA PERENDAMAN DAN TINGKAT KONSENTRASI EKSTRAK BAWANG MERAH (Allium cepa L.) TERHADAP PERTUMBUHAN STEK TANAMAN NILAM (Pogostemon cablin BENTH.) - Rahmani, Dia Ayu; Karno, Karno; Kristanto, Budi Adi (Universitas Muslim Indonesia, 2021)
Patchouli (Pogostemon cablin Benth.) is a plantation crop which produces essential oil. Sidikalang patchouli variety has not yet been able to reach the maximum yield, it just 13,66 ton/ha. The causes is difficulty of cultivating patchouli generatively. Field experiment were carried out to evaluate the length of soaking time and concentration level of shallot extract (Allium cepa L.) on patchouli cuttings growth in the filed of Bumi Rejo Farmer Group, Cendana, Purbalingga from September to October 2019. The experiment was set up as a 4x4 factorial design in a Completely Randomized Design (CRD) with 10 replications. The first factor was long cuttings immersion (minutes) P1: 60, P2: 90, P3: 120, and P4: 150. The second factor is concentration level (%) T0 : control, T1 : 25, T2 : 50, dan T3 : 75. The data obtained were evaluated using analysis of variance (ANOVA) to determine the effect of treatments applied continued with Duncan’s Multiple Range Test (DMRT) at 5% signficance level to determine the differences between treatment. The length of shallot extract soaking time treatment had no effect on all parameters. The concentration level treatment had a significant effect on the parameters of shoot length and total number of shoots. The interaction had a significant effect on the total number of leaves